A Contrastive Analysis Of Vowel In Indonesian and English - Margrettha Is Sirait; Yevana Arthika Hutagaol; Putra Pranata Simanjuntak; Anita Sitanggang (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
This article discusses English and Indonesian Vocal Analysis. Because there are so many linguistic elements in both languages, the researcher tries to investigate the phonetic aspects of the languages. This article uses a qualitative descriptive research design which elaborates and describes the overall perspective of how the sound of each element of language changes when it is spoken and what exactly conveys different meanings. Researchers used literature review as a data collection technique. The data source comes from the Bruno Mars song entitled Count on Me. This article adopts the CA technique or Contrastive Analysis to analyze the data and found differences in Indonesian and English vowels. It can be seen from the word structure that changes and so does the phonetic transcription which results in significant differences as well.